2015
DOI: 10.1038/srep15584
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin- and low pH-mediated fusogenicity of avian metapneumovirus fusion proteins is determined by residues at positions 100, 101 and 294

Abstract: Avian metapneumovirus (aMPV) and human metapneumovirus (hMPV) are members of the genus Metapneumovirus in the subfamily Pneumovirinae. Metapneumovirus fusion (F) protein mediates the fusion of host cells with the virus membrane for infection. Trypsin- and/or low pH-induced membrane fusion is a strain-dependent phenomenon for hMPV. Here, we demonstrated that three subtypes of aMPV (aMPV/A, aMPV/B, and aMPV/C) F proteins promoted cell-cell fusion in the absence of trypsin. Indeed, in the presence of trypsin, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…In a previous study, we demonstrated that the cleavage of aMPV/B F protein is independent of exogenous trypsin (34). Here, we investigated the effect of adding trypsin on replication of aMPV/B.…”
Section: Ampv/b Grows In Vitro Without the Addition Of Trypsinmentioning
confidence: 93%
See 2 more Smart Citations
“…In a previous study, we demonstrated that the cleavage of aMPV/B F protein is independent of exogenous trypsin (34). Here, we investigated the effect of adding trypsin on replication of aMPV/B.…”
Section: Ampv/b Grows In Vitro Without the Addition Of Trypsinmentioning
confidence: 93%
“…Syncytium formation assay to measure fusogenicity of the F protein. The syncytium formation assay was performed to analyze F protein fusogenic activity as previously described (34)(35)(36). Vero cells grown in 6-well plates to 85% confluence were transfected with 1 g plasmid carrying the F gene with ExFect transfection reagent (Vazyme Biotech, Nanjing, China) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The entry of paramyxoviruses into the cell is thought to occur at the cell surface in a low pH-independent manner, a mechanism that requires the binding of the envelope glycoproteins to its receptors to activate membrane fusion of the virus and cell (38). Our prior work has demonstrated that residue His 294 is responsible for aMPV/B F protein-mediated cell-cell fusion independent of low pH (42), suggesting that the aMPV/B F protein attachment to integrin leads to cell-surface fusion. Further investigation is needed to determine whether the entry of aMPV/B occurs at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the aMPV F protein alone can induce cell-cell fusion (41,42), suggesting that aMPV F protein has the function for binding to its receptor(s). A series of sequence/structure analysis, blockade, knockdown, overexpression, and mutagenesis experiments demonstrated that integrin is a functional receptor for the aMPV/B F protein, which induces cell-cell fusion and aMPV/B infection.…”
Section: Discussionmentioning
confidence: 99%